Robotic deep inferior epigastric perforator flap harvest in breast reconstruction. Issue 4 (5th January 2022) - Daar, David A.; Anzai, Lavinia M.; Vranis, Neil M.; Schulster, Michael L.; Frey, Jordan D.; Jun, Min; Zhao, Lee C.; Levine, Jamie P.
Abstract: Introduction: Reducing donor site morbidity after deep inferior epigastric artery perforator (DIEP) flap harvest relies mainly upon maintaining integrity of the anterior rectus sheath fascia. The purpose of this study is to describe our minimally‐invasive technique for robotic DIEP flap harvest. Methods: A retrospective review of four patients undergoing seven robotic‐assisted DIEP flaps from 2019 to 2020 was conducted. Average patient age and BMI were 52 years (range: 45–60 years) and 26.7 kg/m 2 (range: 20.6–32.4 kg/m 2 ), respectively. Average follow‐up was 6.31 months (range: 5.73–7.27 months). Robotic flap harvest was performed with intramuscular perforator dissection in standard fashion, followed by the transabdominal preperitoneal (TAPP) approach to DIEP pedicle harvest using the da Vinci Xi robot. Data was collected on demographic information, perioperative characteristics. Primary outcomes included successful flap harvest as well as donor site morbidity (e.g., abdominal bulge, hernia, bowel obstruction, etc.). Results: All four patients underwent bilateral abdominally‐based free flap reconstruction. Three patients received bilateral robotic DIEP flaps, and one patient underwent unilateral robotic DIEP flap reconstruction. The da Vinci Xi robot was used in all cases. Average flap weight and pedicle length were 522 g (range: 110–809 g) and 11.2 cm (range: 10–12 cm), respectively. There were no flap failures, and no patient experienced abdominal wall donor site morbidity on physical exam. Conclusion: While further studies are needed to validate its use, this report represents the largest series of robotic DIEP flap harvests to date and is a valuable addition to the literature.